Identity-based encryption scheme against adaptive leakage - Jia-hui TANG; Yan-qin ZHU; Xi-zhao LUO (Tongxin xuebao)
In allusion to the problem that scheme resilient to adaptive leakage was lacked in identity-based encryption,a notion of entropic leakage-resilient was used to define the security against adaptive leakage in IBE.Then by using identity-based hash proof system and extractors,an adaptive-leakage secure IBE scheme was proposed.And for instantiation,an IBE scheme against adaptive leakage based on q-TABDHE assumption was constructed.Security analysis shows that the scheme achieves chosen-plaintext attack security,and it can not only resist adaptive leakage effectively,but also tolerate more key leakage.